Growth performance, reproductive parameters and fertility measures in young Nellore bulls with divergent feed efficiency - Rossi, Guilherme Fazan [UNESP]; Bastos, Natália Marins [UNESP]; Vrisman, Dayane Priscila [UNESP]; Rodrigues, Naiara Nantes [UNESP]; Vantini, Roberta [UNESP]; Garcia, Joaquim Mansano [UNESP]; Dias, Erika Aline Ribeiro; Simili, Flávia Fernanda; Guimarães, André Lasmar; Canesin, Roberta Carrilho; Mercadante, Maria Eugênia Zerlotti; Freitas-Dell’Aqua, Camila de Paula [UNESP]; et al. (FapUNIFESP (SciELO), 2022)
The growth, sexual maturity and fertility-related parameters related of young Nellore bulls with divergent residual feed intake (RFI) raised on pasture were evaluated. After classification of 48 young males as low and high RFI (more and less efficient, respectively), the animals were evaluated for growth and reproductive parameters at 28-day intervals from 14.3 to 24.6 months of age. The semen was cryopreserved in the last sampling and fresh and post-thaw semen samples were evaluated. Low RFI bulls exhibited higher initial and final body weight (P < 0.05), but feed intake, body condition score and growth measures evaluated by carcass ultrasound were unaffected by RFI (P > 0.05). The scrotal circumference, sperm concentration, defects, and quality of fresh semen, and ultrasonographic testicular characteristics were unaffected by RFI (P > 0.05). However, velocity parameters such as average path and curvilinear velocities determined by computer-assisted sperm analysis of thawed semen submitted to the rapid thermoresistance test were improved (P < 0.05) in low RFI bulls, but this improvement in quality did not enhance in vitro sperm fertilizing ability. Our results demonstrated significant differences in metabolism and growth performance between bulls of divergent RFI. In addition, there was slight improvement in the semen quality of bulls with low RFI bulls, but this did not enhance in vitro fertilizing ability. Selection of beef bulls for RFI can be performed, which will result in economic benefits by improving the growth performance of the animals without affecting reproductive parameters.
Keywords: Bovine; Embryo; Male; Residual feed intake; Semen.